Research on the half complementary split‐ring resonator and its application for designing miniaturized patch antenna. Issue 11 (November 2015) - Cai, Yang; Qian, Zuping; Cao, Wenquan; Zhang, Yingsong
ABSTRACT In this letter, a novel half complementary split‐ring resonator (HCSRR) is investigated, and the employment for designing miniaturized patch antenna is researched. Through parameter‐study, the proposed HCSRR shows almost the same resonant characteristic as the original CSRR structure. When the half‐miniaturized CSRR is sandwiched in the middle of half patch antenna, which sharing the same virtual magnetic wall with HCSRR, the resonant frequency of the patch antenna can be lowered in a much degree. To validate the proposed concept, the miniaturized antenna operating at 2.21 GHz is fabricated and measured. The measured results show good accordance with the simulated ones and stable radiation pattern of patch mode can be maintained, which validate the characteristic of the proposed HCSRR structure. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2601–2604, 2015